Gamification for staff motivation: Impact on work efficiency and corporate culture at the international level - Getman Anatolii P.; Yaroshenko Oleg M.; Demenko Olga І.; Lutsenko Оlena Yе.; Prokopiev Roman Ye. (Journal of Economics and Management)
Aim/purpose – This article analyzes the impact of gamification on staff motivation, performance, and corporate culture at the international level. It also examines the integration of advanced technologies such as AI (artificial intelligence), AR (augmented reality), and VR (virtual reality) into gamification strategies to enhance their effectiveness.